Immune-Complex Mediated Crescentic Membranoproliferative Glomerulonephritis Presenting as Rapidly Progressive Renal Failure: A Case Report (Bangladesh Renal Journal, 2026)
Rapidly progressive glomerulonephritis represents a spectrum of diseases characterized by crescent formation in glomeruli and rapid decline in renal function. Membranoproliferative glomerulonephritis (MPGN) with crescentic transformation is rare and often presents with severe renal impairment. We report a case of a 40-years hypertensive woman who initially presented with acute kidney injury (AKI) and was treated as acute pyelonephritis. Due to rapid deterioration of renal function requiring hemodialysis, she was evaluated for RPGN. Renal biopsy revealed immune-complex mediated crescentic MPGN. Early aggressive immunosuppressive therapy resulted in significant renal recovery and dialysis independence.Bang. Renal J. 2026; 8(1): 38-41